Metformin-Associated Lactic Acidosis following Intentional Overdose Successfully Treated with Tris-Hydroxymethyl Aminomethane and Renal Replacement Therapy. (5th July 2012) - Lam, Ngan; Sekhon, Gurbir; House, Andrew A.
Abstract : A 43-year-old woman was brought to the hospital with severe metabolic acidosis (pH 6.56, bicarbonate 3 mmol/L, and lactate 18.4 mmol/L) and a serum creatinine of 162  μ mol/L with a serum potassium of 7.8 mmol/L. A delayed diagnosis of metformin-associated lactic acidosis was made, and she was treated with tris-hydroxymethyl aminomethane (THAM) and renal replacement therapy (RRT). Following a complete recovery, she admitted to ingesting 180 tablets (90 grams) of metformin. Her peak serum metformin concentration was 170  μ g/mL (therapeutic range 1-2  μ g/mL). Our case demonstrates an intentional metformin overdose resulting in lactic acidosis in a nondiabetic patient who was successfully treated with THAM and RRT.